Analysis on Social Networking - Nasa, Kanika; Sharma, Upasana (International Journal of Computer Sciences and Engineering, 2014)
Social Networking deals with connecting people through a common media. It builds links and a lot of algorithms are present to find the literatures in the links created. The most basic issue that is produced from this innovation is the abundance in the links. The concern is to figure out the interestingness in the links and the uniqueness it provides in each subject. We have used real world data for testing and creating output with interesting results.